Evaluating of the activity antioxidant and fatty acids profile of lychee seeds (Litchi chinensis SONN.) - Luzia, débora Maria Moreno [UNESP]; Jorge, Neuza [UNESP] (Emerald, 2011)
Purpose: The purpose of this paper is to characterize lychee seeds regarding their centesimal composition, and also to evaluate their antioxidant potential and fatty acid profile. Design/methodology/approach: To obtain the extract, dehydrated and grinded seeds were extracted with ethyl alcohol for 30 min, at a proportion of 1:3 of seeds:ethyl alcohol, under continuous agitation, at room temperature. Afterwards, the mixture was filtered and the supernatant subjected to a rotoevaporator at 40oC aiming to determine, by direct weighing, the extract dry matter yield. Findings: The largest found values went to the total carbohydrates (72.75 percent). In the oil from the lychee seeds there was a high percentage of unsaturated fatty acids, the main component being linoleic, considered an essential fatty acid. Research limitations/implications: Implies the identification of compounds biativos extracted from seeds of tropical and subtropical fruits, and to prevent certain types of diseases. Originality/value: The article tries to identify new source of phenolic compounds extracted from fruit. © Emerald Group Publishing Limited.
Keywords: Bioactive composition; Brazil; DPPH; Extract; Fruits; Gas-chromatography; Litchi chinensis